Ācārya Śaṅkara and His Brahma-Sūtra: A Realistic Approach - Panda, Prajna; Panda, Narasingha Charan (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2019)
Ācārya Śaṅkara was a great philosopher of ancient India. He was most renowned exponent of the Advaita Vedānta School of philosophy, from whose doctrines the main currents of modern Indian thought are derived. He has propagated Advaita Vedānta. According to Ācārya Śaṅkara, there is one Absolute Brahman, who is known as Sat-Cit-Ānanda-- who is of an absolutely homogeneous nature. The appearance of this World is due to Māyā -- the illusory power of Brahman which is neither Sat (true) nor Asat (false). This World is also unreal. Ācārya Śaṅkara travelled widely in India and preached his Advaita philosophy wherever he went. He taught that supreme Brahman is Nirguṇa (without the guṇas), Nirākāra (formless), Nirviśeṣa (without attributes) and Akartā (non-agent). Brahman is above all needs and desires. This paper will highlight all about the Vedāntic Philosophy of Śaṅkara as described in his Brahma Sūtra.